What predicts Australian university students' intentions to volunteer their time for community service?. (5th February 2013) - Hyde, Melissa K.; Knowles, Simon R.
Abstract: University students represent one target population with great potential to serve as volunteers. The primary focus on describing the characteristics of students who choose to volunteer, however, has resulted in limited understanding of the psychosocial factors impacting on students' decisions to volunteer. To bridge this gap, we used an extension of a well‐known theoretical framework, the theory of planned behaviour (TPB), to predict students' intentions to volunteer for community service. Using content and thematic analysis, we explored also students' motivations and constraints for volunteering. Students ( N = 235; M age = 22.09 years) self‐reported their attitude, normative influences, control perceptions, moral obligation, past behaviour, demographic characteristics, and intentions for volunteering via questionnaire. Regression analyses showed that the extended TPB explained 67% of the variance in students' volunteering intentions. In qualitative analyses, themes primarily represented the factors contributing to low efficacy for volunteering (e.g., time constraints). Control perceptions and perceived moral obligations related to volunteering represent important future targets to encourage student volunteering for organisations providing critical services for those most in need.